2014
DOI: 10.1038/nm.3514
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal targets for reducing mutant huntingtin expression to ameliorate disease in a mouse model of Huntington's disease

Abstract: Huntington’s disease (HD) is a fatal dominantly inherited neurodegenerative disorder caused by a CAG repeat expansion leading to an elongated polyglutamine stretch in Huntingtin1. Mutant Huntingtin (mHTT) is ubiquitously expressed but elicits selective cortical and striatal neurodegeneration in HD2. The mechanistic basis for such selective neuronal vulnerability remains unclear. A necessary step towards resolving this enigma is to define the cell types in which mHTT expression is causally linked to the disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
152
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 181 publications
(165 citation statements)
references
References 37 publications
12
152
0
Order By: Relevance
“…Moreover, a recent study using BACHD mice showed that disease phenotypes can only be fully rescued when mutant Htt is deleted from both the cortex and striatum, demonstrating the distinct yet interacting roles of cortical and striatal mutant Htt in HD (Wang et al, 2014). We found that the striatal connections in Htt cortical cKO remain stronger and numerous in 5 week mice even though intracortical connectivity of layer 5 neurons in these mice is diminishing.…”
Section: Htt Is Required To Mold the Circuitry Of The Cortex Striatumentioning
confidence: 52%
“…Moreover, a recent study using BACHD mice showed that disease phenotypes can only be fully rescued when mutant Htt is deleted from both the cortex and striatum, demonstrating the distinct yet interacting roles of cortical and striatal mutant Htt in HD (Wang et al, 2014). We found that the striatal connections in Htt cortical cKO remain stronger and numerous in 5 week mice even though intracortical connectivity of layer 5 neurons in these mice is diminishing.…”
Section: Htt Is Required To Mold the Circuitry Of The Cortex Striatumentioning
confidence: 52%
“…We showed that individual CCT subunits reduced mHTTQ97 in PC12 cells and that CCT3 and ApiCCT1 reduced mHTT in BACHD neurons. Targeting the levels of mHTT to reverse salient features of HD pathogenesis has been suggested by others (59)(60)(61) and has been supported by elegant studies demonstrating that reducing mHTT expression in BACHD neurons improves HD-relevant phenotypes (6,55). Further work will be needed to define the mechanism(s) by which mHTT induces HD pathogenesis and what role is played by deficits in BDNF transport and signaling.…”
Section: Impaired Lysosome Transport In Bachd Cortical Neurons Wasmentioning
confidence: 95%
“…It has been shown that mHTT has an impact on axonal trafficking and signaling, synaptic function, gene expression, mitochondrial function, calcium homeostasis, and proteostasis (4,5). Thus, mHTT plays a central role in HD pathogenesis, an assertion fully supported by recent studies in the BACHD model of HD (6).…”
mentioning
confidence: 85%
“…ACCEPTED MANUSCRIPT 20 whereas reduction of mhtt in both cortical and striatal populations ameliorates all behavioural deficits and the selective brain atrophy [176]. Moreover, abnormal fat cell function has been reported in several mouse models of HD.…”
Section: Accepted Manuscriptmentioning
confidence: 99%